IDENTIFICATION AND COMPOSITION OF FEEDING PLANTSPECIES OF SIMAKOBU MONKEYS (Simias concolor) IN NORTHERN SIBERUT, MENTAWAI ARCHIPELAGO - Nurul Silva Lestari; wendy Erb (Pusbindiklat - LIPI, 2011)
The availability of food resources is one of habitat components that support simakobu conservation. This study was aimed to identify the species and composition of feeding plants and habitat structures of simakobu. Habituation of simakobu was conducted in prior to the study. Afterwards it was performed to collect the data on species and composition of feeding plants of simakobu using ad libitum methods. Determination of the structure and composition of vegetation on simakobu habitat, vegetation analysis was done by establishing plot measuring all long 100 m for 15 plots. Result showed that amount of 116 plant species was eaten by simakobu. Katatairek (Bhesa paniculata), logauna (Knema sumatrana) and ungla (Aporosa symplocoides) were species that its parts were most widely used as food source of simakobu. Young leaves, leaf bud, ﬂ ower and fruit parts of those speciesare eaten by simakobu. This study suggests that the dominant plant species on the simakobu habitat is Logauna (Knema sumatrana).